Analytical Study in Light of the Jordanian and English Arbitration Laws - Riad Al-Rabadi, Dr. Najm (2021)
The legislator seeks to review and amend economic legislations that contribute to creating a legislative environment which commensurate with economic and commercial developments. Among these legislations is the Jordanian Arbitration Law No. (13) of (2001) amended by Law No. (16) of (2018), which aims to provide safeguards to the parties to the arbitration during the process in all its stages, from the arbitration agreement to the issuance of the arbitration decision and the possibility of appeal.